Learning a Foreign Language under the Influence of Parents: Parental Involvement and Children's English Learning Motivational Profiles. - Choi, Naya; Jung, Suji; No, Boram (Journal of Child & Family Studies, 2024)
This study aimed to identify the English learning motivational profiles of elementary-school-aged children based on self-determination theory and to verify if parental involvement can predict a child's English learning motivational profile classification. In a sample of 539 South Korean elementary-school-aged children, latent profile analysis revealed four English learning motivational profile groups: (1) children with the highest levels of intrinsic and extrinsic motivation and the lowest level of amotivation (high quantity), (2) children with a comparatively high level of extrinsic motivation and comparatively low levels of intrinsic motivation and amotivation (low quality with low amotivation), (3) children with comparatively high levels of extrinsic motivation and amotivation coupled with a low level of intrinsic motivation (low quality with high amotivation), and (4) children with the lowest levels of intrinsic and extrinsic motivation coupled with the highest level of amotivation (low quantity). In addition, we found children's English learning motivational profiles can be predicted by parental involvement. The results indicate that when parents respect children's learning style, offer learning information, and provide emotional support, children are more likely to have better quality or higher quantity motivational profiles. Conversely, parental pressure was related to worse quality or lower quantity motivational profiles. The implications of the study are discussed in terms of South Korean parent-child relationships and the English as a Foreign Language (EFL) context. Highlights: The "high quality" motivational profile, characterized by high intrinsic and low extrinsic English learning motivation, was not found in South Korean children. Amotivation is a key dimension of difference in South Korean children's motivational profiles. Emotionally and cognitively supportive parental involvement has positive effects on children's English learning motivational profiles, whereas parental pressure has negative effects on it.